Association between IL‐4 tagging single nucleotide polymorphisms and the risk of lung cancer in China. Issue 4 (6th February 2019) - Tan, Nan; Song, Jiangjiang; Yan, Mengdan; Wu, Jiamin; Sun, Yao; Xiong, Zichao; Ding, Yipeng
Abstract: Background: In China, lung cancer is also the most commonly diagnosed cancer with a lower 5‐year survival rate, leading to high social burdens. Recently, many studies highlighted the importance of inflammation in the initiation and progression of cancer. The goal of this study was to investigate the association between interleukin‐4 ( IL‐4, OMIM#147780) single nucleotide polymorphisms (SNPs) and lung cancer susceptibility. Methods: A case‐control study was conducted in a Chinese population including 199 male patients with lung cancer and 266 healthy men. Six SNPs selected from the HapMap database were genotyped using Agena MassARRAY. Genetic models and haplotype analyses were utilized to evaluate the association between SNPs and lung cancer risk. Results: In our findings, rs2243250 was associated with a decreased lung cancer risk under the log‐additive model (odds ratio, OR = 0.71, 95% confidence interval, CI = 0.51–0.97, p = 0.030), and the G/G genotype of rs2227284 conferred a negative effect; the risk of lung cancer under the codominant (OR = 0.19, 95% CI = 0.04–0.87, p = 0.040) and recessive models (OR = 0.20, 95% CI = 0.04–0.88, p = 0.012) after adjusted by age. Conclusions: These data indicated potential associations between IL‐4 polymorphisms and lung cancer susceptibility. That may help to improve the understanding of the relationship between inflammation and lung cancer in the future. Abstract : Association between IL‐4 polymorphisms and lung cancer susceptibility. Rs2243250, rs2243267 and rs2227284 were associated with decreased lung cancer risk. These findings provide information for the diagnosis and prognosis of lung cancer.